The first balloon-borne sample analysis of atmospheric carbonaceous components reveals new insights into formation processes. (June 2023) - Benoit, Roland; Vernier, Hazel; Vernier, Jean-Paul; Joly, Lilian; Dumelié, Nicolas; Wienhold, Frank G.; Crevoisier, Cyril; Delpeux, Sandrine; Bernard, François; Dagaut, Philippe; Berthet, Gwenaël
Abstract: Atmospheric aerosol optical, physical, and chemical properties play a fundamental role in the Earth's climate system. A better understanding of the processes involved in their formation, evolution, and interaction with radiation and the water cycle is critical. We report the analysis of atmospheric molecules/particles collected with a new sampling system that flew under regular weather balloons for the first time. The flight took place on January 18, 2022 from Reims (France). The samples were subsequently analyzed by high-resolution mass spectrometry (Orbitrap) to specifically infer hundreds of organic components present in 4 different layers from the troposphere to the stratosphere (up to 20 km). Additional measurements of O3, CO, and aerosol concentrations a few hours before this flight took place to contextualize the sampling. After separating common species found on each filter that might be common to atmospheric layers or residuals for contaminations, we found that each sample yields significant differences in the number and size of organic species detected that should reflect the unique composition of atmospheric layers. While tropospheric samples yield significantly oxidized and saturated components, with carbon numbers below 30 that might be explained by complex organics chemistry from local and distant source emissions, the upper tropospheric and stratospheric samples were associated with increased carbon numbers (C > 30), with a significantly reduced unsaturation number for the stratosphere, that might be induced by strong UV radiations. The multimodal distributions of carbon numbers in chemical formulas observed between 15 and 20 km suggest that oligomerization and growth of organic molecules may take place in aged air masses of tropical origin that are known to carry organic compounds even several km above the tropopause where their lifetime significantly increases. In addition, the presence of organics may also reflect the extended influence of wildfires smoke injected during the spring and summer in the NH hemisphere before the in situ observations and their long-lifetime in the upper troposphere and stratosphere. Graphical abstract: Photographic credit: Marc Fourmentin - Laboratoire de PhysicoChimie de l'Atmosphère. Image 1 Highlights: Unique launching infrastructure in Europe (Reims/France) to operate state-of-the art atmospheric instruments New balloon-borne sampling device to characterize the chemical composition of organics (troposphere to stratosphere) Offline analysis reveals the growth of organics aerosol in the stratosphere Organics aerosol could derive from oligomerization processes along transport from the tropics and/or influenced by wildfires